HARI-HARA: TRADITION OF SYNCRETISM IN SOUTH EAST ASIA SPECIAL REFERENCE TO BRAHMAPUTRA VALLEY - Baruah, Chinmoy Jyoti; Patowary, Kamal Nayan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research article aims at examining the tradition of syncretism in Southeast Asia with a special reference to the region of the Brahmaputra Valley and in connection with the deity Hari-Hara. Eclecticism implies the integration of various information flows, religious, cultural, and philosophical, which has been traditionally significant for the formation of spiritual and social models in the areas with interactions of several traditions. In Southeast Asia particularly the Khmer Empire, the syncretism of Shaivism and Vaishnavism together with Hindu and Buddhists is evident in the worship of Hari-Hara; Vishnu- Shiva. This syncretic practice was not only a sign of religious tolerance but also expressed political power and social integration under kings such as Jayavarman VII embodied in temple architectures including Angkor Wat and Bayon temples. By contrast, the case of the Brahmaputra Valley in India can be singled out as the example of syncretism between tribal and Brahmanical practices when the local indigenous cults were gradually intertwined with the Hindu ones and produced such localized forms of Hari-Hara. The Deopani Hari-Hara sculptures of the Doiyang Dhansiri Valley elucidate the syncretization of classical Brahmanical elements with tribal regional forms. While syncretism in the Khmer Empire was more political, more centrally driven and less successful than the one in the Brahmaputra Valley which was predominantly the result of protracted social contact and the Bhakti movement’s stress on individual devotion and tolerance. The research article also shows how Hari-Hara became an important identity for religious and cultural syncretism in both regions, allowing the harmonious interaction of different religions and improving political authority. Analyzing artistic, architectural and socio-political aspects of Hari-Hara worship in this study reveals the values of syncretism as a function of integrationist in maintaining social cohesion as well as preserving the political authority. Finally, the comparison of the Brahmaputra Valley with mainland Southeast Asia brings further understanding of the processes that produce and sustain syncretic religious cultures, enriching religious diverse topographies of these areas.